Systematic Literature Review Application of The Unified Modeling Language (UML) Method in Designing a New Student Admission Information System: Systematic Literature Review Application of The Unified Modeling Language (UML) Method in Designing a New Student Admission Information System - Putri, Fazia (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2024)
In this study, a systematic literature review that focuses on the application of the UML method in designing a New Student Admission Information System. Where in this study raised problems experienced by several schools that still use the old system (manual) in operating activities in schools, one of which is the flow of new student admissions. So that it produces performance that is not effective and efficient and has an unfavourable impact on the school. Therefore, the need for tools in modelling in designing academic processes in schools, namely by using UML (Unified Modeling Language). UML is a standard language used to model, design, and document software systems. The types of diagrams used in UML are Use Case Diagrams, Class Diagrams, Activity Diagrams, and Sequence Diagrams which can help in modeling the flow of new student admissions. The results of the literature review that has been carried out, it can be concluded that using UML in modeling in designing academic processes in schools has a positive impact and makes it easier to present better and more up-to-date information.